Pengaruh Inovasi Produk, Promosi, Dan Kualitas Produk Terhadap Volume Penjualan Kopi Liberika Tungkal Di Gerai UMKM Mekar Jaya Kecamatan Betara - Dandi Palaguna; Agustina Mutia; Ahmad Syahrizal (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine how the effect of product innovation, promotion, and product quality on the sales volume of Liberika Tungkal coffee at the Mekar Jaya UMKM Outlet, Betara District. The population in this study are all consumers or customers who buy processed Liberika Tungkal coffee products. The sampling technique used the Lame Show formula with a total of 96.4 and rounded up to 100 people. Data collection techniques using questionnaires, documentation, observations and interviews. Which research method used quantitative methods, this study uses primary data and secondary data with multiple linear regression model. Based on the results of the data analysis test, it can be concluded that partially (T test) the product innovation variable (X1) has no effect on sales volume (Y), promotion variable (X2) has a positive effect on sales volume (Y), product quality variable (X3 ) has a positive effect on sales volume. Simultaneously (Test F), shows that product innovation (X1), promotion (X2), and product quality (X3) simultaneously or simultaneously have a positive and significant effect on sales volume (Y). The influence of the variable (Coefficient of Determination) product innovation, promotion, and product quality is 68.1%, while the remaining 31.9% is influenced by other variables not examined in this study.